Investigation on welding sequence of I-beam by hybrid inversion. (November 2018) - Bai, Ruixiang; Guo, Zhenfei; Tian, Chenguang; Lei, Zhenkun; Yan, Cheng; Tao, Wang
Abstract: A thermal-mechanical model based on welding experiment and finite element (FE) method was developed for welding deformation analysis and welding sequence optimization of arc welding process used in hull steel structure forming process. By means of digital image correlation (DIC) and electrical measurement method, the deformation of T-beam was measured, and the equivalent heat source parameter (EHSP) was inversed by an optimization algorithm. The purpose of the inversion is to match the numerical results with the experiment results, so the EHSP has taken account into the influence of various factors on the welding deformation and residual stress. Thus, the developed method can avoid using the highly physical nonlinearity algorithm when considering the complex material constitutive and phase transformation process, which greatly improves the efficiency of calculation. Finally, the EHSP obtained from the hybrid inversion is applied to investigate the influence of welding sequence on welding deformation and residual stress in I-beam. This method can be applied to other metal materials and weld form. Highlights: An equivalent heat source parameter was proposed to consider the influence of welding deformation and residual stress. Welding deformation of T-section beam was measured using digital image correlation and electrical measurements. The equivalent heat source parameter was reversed by a combination of FEM and experimental measurements of T-section beam. The influence of welding sequence on welding deformation and residual stress of I-section beam was studied.